2019
DOI: 10.1016/j.jdent.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of digital intraoral scanners at measuring early erosive wear

Abstract: Objectives: To investigate the sensitivity of intraoral scanners to quantitatively detect early erosive tooth wear. Methods: Natural buccal enamel samples were mounted in acrylic and scanned at baseline with an intraoral scanner (3M True Definition Scanner, 3M, USA). Samples were then exposed to 0.3% citric acid pH 3.2 at intervals of 10 minutes up to a total of 120 minutes and scanned after each exposure resulting in analysis of 13 datapoints per sample. Each scan was aligned with the baseline and data points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…By combining measurement error and uncertainty, surface profile differences>0.035mm represent true tooth substance loss. Taking into account that the accuracy of a long span 3D model, as featured in this study, is lower compared to single tooth models, we can foresee even smaller measurement error and uncertainty if the same method is tested on single tooth models [20,21,25,28]. Accordingly, larger measurement error and uncertainty are expected in full-arch 3D models [28].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…By combining measurement error and uncertainty, surface profile differences>0.035mm represent true tooth substance loss. Taking into account that the accuracy of a long span 3D model, as featured in this study, is lower compared to single tooth models, we can foresee even smaller measurement error and uncertainty if the same method is tested on single tooth models [20,21,25,28]. Accordingly, larger measurement error and uncertainty are expected in full-arch 3D models [28].…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, larger measurement error and uncertainty are expected in full-arch 3D models [28]. Furthermore, it is worth mentioning that no powder was needed for scanning with the IOS system used, a notable point as a previous study reported part of the measurement error had resulted from the presence of powder on the surfaces of interest [21].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations